2006
DOI: 10.1038/sj.onc.1209613
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cellular senescence by Rb2/p130

Abstract: Growth regulatory functions of Rb2/p130, which aim at a sustained arrest such as in quiescent or differentiated cells, qualify the protein also to act as a central regulator of growth arrest in cellular senescence. In this respect, Rb2/ p130 functions are connected to signaling pathways induced by p53, which is a master regulator in cellular senescence. Here, we summarize the pathways, which specify pRb2/p130 to control this arrest program and distinguish its functions from those of pRb/p105.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 90 publications
2
21
0
Order By: Relevance
“…Given that we found HP1-g expression in p53-deficient tissue in our model, the Rb pathway may be involved in the ability of p16 to promote senescence. The Rb2/p130 protein, which is a member of the Rb family, is also reported to mediate the senescent growth arrest (Helmbold et al, 2006). Similar to pRb, Rb2/p130 is hyperphosphorylated by cyclin D/cdk4 or 6 and cyclin E or A/cdk2 complexes and considered acting as a master regulator of pRb in a sustained senescent arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Given that we found HP1-g expression in p53-deficient tissue in our model, the Rb pathway may be involved in the ability of p16 to promote senescence. The Rb2/p130 protein, which is a member of the Rb family, is also reported to mediate the senescent growth arrest (Helmbold et al, 2006). Similar to pRb, Rb2/p130 is hyperphosphorylated by cyclin D/cdk4 or 6 and cyclin E or A/cdk2 complexes and considered acting as a master regulator of pRb in a sustained senescent arrest.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that ectopic expression of RNPC1a markedly increased the number of cells that stained positive with senescence-associated ␤-galactosidase (SA-␤-Gal) (Fig. 9B) concomitantly with increased expression of senescence markers p130 and DEC1 (14) (Fig. 9A, compare lanes 1 and 3 with 2 and 4, respectively).…”
Section: Rnpc1mentioning
confidence: 96%
“…Activation of the Rb pathway has been implicated in senescence and there is experimental evidence that pRb may play a direct role in gene silencing during induction of senescence (29,35). Because pRb levels are dramatically reduced in nutlintreated cells (Fig.…”
Section: Discussionmentioning
confidence: 99%